Analisa Penggunaan WebRTC dan Websocket pada Real Time Multiplayer Online Game Tradisional Ceki - Prathama, Gede Humaswara; Ary Esta Dewi Wirastuti, Ni Made; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2019)
Ceki is one of the traditional card games that has been quite popular in Malaysia, Singapore and Indonesia. In Bali the game of ceki has become a tradition, where the game is played when there is community activity. Multiplayer online games are one way to introduce and develop traditional games to be more interesting to play. The problems that are often faced to develop multiplayer online games include the latency problems that are different from each player so that it can interfere with games from other players who have better latency. In this study, a real time multiplayer online game will be built to play traditional games. discussing how the rules of traditional games obtained from the rules of the Balinese game will be applied to the game engine from online multiplayer games, how to implement online game multiplayer architecture on client-server and peer to peer web-browsers. The focus of this research is on the performance of the use of websocket and webRTC on latency and bandwidth usage for data synchronization that supports real time multiplayer online games based on peer to peer. The results obtained from this study see the average latency needed to synchronize data between websocket compared to webRTC is very significant. The number of players has no effect on latency in both websocket and webRTC.